DMSO-free cryopreservation of hiPSC-derived cardiomyocytes: low temperature characterization and protocol development - Akshat S. Mallya; Tessa Burrows; Jeanne Hsieh; Troy Louwagie; James R. Dutton; Brenda M. Ogle; Allison Hubel (Stem Cell Research & Therapy)
Abstract Background Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have attracted significant interest for use in disease modeling, drug discovery and potential therapeutic applications. However, conventional hiPSC-CM cryopreservation protocols largely use dimethyl sulfoxide (DMSO) as the cryoprotectant (CPA), which is linked with a loss of post-thaw recovery and function for various cell types and is not ideal for therapeutic protocols. Additionally, the effect of freezing parameters such as cooling rate and nucleation temperature on post-thaw recovery of hiPSC-CMs has not been explored. Methods hiPSC-CMs were generated by Wnt pathway inhibition, followed by sodium l-lactate purification. Subsequently, biophysical characterization of the cells was performed. A differential evolution (DE) algorithm was utilized to determine the optimal composition of a mixture of a sugar, sugar alcohol and amino acid to replace DMSO as the CPA. The hiPSC-CMs were subjected to controlled-rate freezing at different cooling rates and nucleation temperatures. The optimum freezing parameters were identified by post-thaw recoveries and the partitioning ratio obtained from low temperature Raman spectroscopy studies. The post-thaw osmotic behavior of hiPSC-CMs was studied by measuring diameter of cells resuspended in the isotonic culture medium over time. Immunocytochemistry and calcium transient studies were performed to evaluate post-thaw function. Results hiPSC-CMs were found to be slightly larger than hiPSCs and exhibited a large osmotically inactive volume. The best-performing DMSO-free solutions enabled post-thaw recoveries over 90%, which was significantly greater than DMSO (69.4 ± 6.4%). A rapid cooling rate of 5 °C/min and a low nucleation temperature of -8 °C was found to be optimal for hiPSC-CMs. hiPSC-CMs displayed anomalous osmotic behavior post-thaw, dropping sharply in volume after resuspension. Post-thaw function was preserved when hiPSC-CMs were frozen with the best-performing DMSO-free CPA or DMSO and the cells displayed similar cardiac markers pre-freeze and post-thaw. Conclusions It was shown that a CPA cocktail of naturally-occurring osmolytes could effectively replace DMSO for preserving hiPSC-CMs while preserving morphology and function. Understanding the anomalous osmotic behavior and managing the excessive dehydration of hiPSC-CMs could be crucial to improve post-thaw outcomes. Effective DMSO-free cryopreservation would accelerate the development of drug discovery and therapeutic applications of hiPSC-CMs.